Development of Learning Methods Basic Life Support Based on E-Learning Program for Nurses: Literature Review - Wijayantha, I Putu Arya; Agustini, Ni Luh Putu Inca Buntari; Diyu, Ida Ayu Ningrat Pangruating; Krisnandari D, Anak Agung Istri Wulan (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Basic Life Support (BLS) training is a must for nurses before entering the world of work. During the establishment of the pandemic in Indonesia, many face-to-face interactions were limited. The limitation also impacts the learning method of nurses. Most of the institutions use the E-learning (online) method. E-learning in nursing study has several advantages, such as being efficient, economical, and flexible. However, it also has disadvantages such as internet access, lack of interaction, and lack of direct practice with the media. This literature review aims to find the best e-learning methods for BLS training. The research design is a literature review. The article was conducted in three journal databases: Google Scholar, Scopus, and PubMed. A total of 16 articles that met the inclusion criteria were reviewed. The study showed that blended learning is the best recommended learning method for BLS. Combined learning methods improve the knowledge and skill performance of the students.